Everyday Encounters with Art: Comparing Expert and Novice Experiences. (October 2016) - Foreman‐Wernet, Lois; Dervin, Brenda
Abstract: The study reported here looked at how two groups of people – one with art expertise and one without – made sense of their encounters with an exhibition of a single artist, the late Paul‐Henri Bourguignon. The study builds on previous research using Dervin's Sense‐Making Methodology to study how people interpret their arts experiences within the contexts of their everyday lives. Informants were asked to rank‐order their selections among the pieces on display according to which had the most impact for them (however they defined impact). Each informant then did a structured qualitative interview focusing on the work he or she chose as most impactful. The researchers looked at thematic elements and other patterns of similarity and difference that arose in the interviews and offer thoughts on how the results of this study may provide insight to those who work in museums.